The use of 24-h ambulatory blood pressure monitoring (ABPM) during the first cycle of sunitinib improves the diagnostic accuracy and management of hypertension in patients with advanced renal cancer - Bamias, A.; Manios, E.; Karadimou, A.; Michas, F.; Lainakis, G.; Constantinidis, C.; Deliveliotis, C.; Zakopoulos, N.; Dimopoulos, M.A. (European Journal of Cancer, 2011)
Aim: Hypertension (HT) complicates treatment with antiangiogenic agents, including the tyrosine kinase inhibitor (TKI) sunitinib. To prospectively evaluate the prevalence and management of HT in patients with advanced renal cell carcinoma (RCC) receiving sunitinib we used 24-h ABPM and we treated HT according to guidelines of the Joint National Committee on Prevention, Detection and Evaluation and the Treatment of High Blood Pressure (JNC7). Patients and methods: Normal 24-h ABPM at the baseline and at 2, 4 and 6 weeks of the first cycle was ensured with the successive use of hydrochlorothiazide + irbesartan, nebivolol and amlodipine. Office BP measurements were used in subsequent cycles to monitor HT. Sunitinib dose was modified only if BP was not controlled with four anti-hypertensive agents. Results: Forty patients were included in this analysis. Twenty-one patients (53%) had baseline HT, while 12 of 14 (84%) normotensive patients required anti-HT treatment during the 1st cycle of sunitinib. HT was infrequent in subsequent cycles and increase of anti-HT medication was required in only 2 cases. Two patients permanently discontinued sunitinib due to HT. The remaining 34 (94%) required no dose modifications for HT. One cardiac event (2.8%) was observed. There was no correlation of HT with sunitinib efficacy. Conclusion: Sunitinib-associated HT is more frequent than previously reported. The use of 24-h ABPM for diagnosis and tailoring of HT according to JNC7 guidelines may achieve uninterrupted, full dose therapy in most patients. The substitution of such protocols for currently used Toxicity Criteria may be warranted. © 2011 Elsevier Ltd. All rights reserved.
Keywords: 24-h ABPM; Hypertension; Renal cell carcinoma; Sunitinib; VEGF